Monitoring an Outcomes-Focused Learning Environment: A Case Study - Aldridge, Jill; Fraser, Barry (Australian Curriculum Studies Association Inc., 2011)
This article reports how teachers in one Western Australian school used a learning environment instrument to assist them in implementing and monitoring the extent to which they were incorporating a more outcomes-focused approach in their teaching. Using a transformational approach to outcomes-focused education, the teachers used a purpose-designed learning environment instrument to provide feedback about students' perceptions to guide improvements in their pedagogical practices. The school supported teachers during the process and used the results to monitor the success of different educational programs in promoting outcomes-focused learning environments. The sample included 449 students in 2001, 626 students in 2002, 471 students in 2003 and 372 students in 2004. There were statistically significant differences between students' perceptions of class room environment from 2001 to 2004 for most scales, as well as differences between each pair of years for specific learning environment scales. When two specific learning areas within the school were compared, there were differences in the degree to which the learning environment had changed between 2001 and 2002.